1982
DOI: 10.1128/jvi.42.2.636-648.1982
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis and Gene Expression in Bacillus subtilis Infected with Wild-Type and Hypermodification-Defective Bacteriophage SP10

Abstract: A hypermodified base (Y-Thy) replaces 20%o of the thymine (Thy) in mature DNA of Bacillus subtilis phage SP10. Two noncomplementing hypermodificationdefective (hmd) mutants are described. At 30°C, hmd phage carried out a normal program, but at temperatures of .37TC, the infection process was nonproductive. When cells were infected at 37°C with hmd phage, DNA synthesis started at its usual time (12 mmin), proceeded at about half the normal rate for 6 to 8 min, and then stopped or declined manyfold. All, or near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…(i) Isopycnic centrifugation. Preliminary evidence obtained during the mutant search (20) showed that no mutant-specific DNA made at 42°C had a normal oxopyrimidine content, and as a result, each should have an atypical buoyant density relative to wt (20,21). Accordingly, mutant phage containing [32P]DNA were prepared at 30°C and used to infect cells at 42°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(i) Isopycnic centrifugation. Preliminary evidence obtained during the mutant search (20) showed that no mutant-specific DNA made at 42°C had a normal oxopyrimidine content, and as a result, each should have an atypical buoyant density relative to wt (20,21). Accordingly, mutant phage containing [32P]DNA were prepared at 30°C and used to infect cells at 42°C.…”
Section: Resultsmentioning
confidence: 99%
“…Identically treated controls were infected with wt. DNA was extracted (2) and banded in neutral CsCl gradients (16,20,21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have likewise demonstrated an inhibitory effect of HMU and other substituted pyrimidines on restriction (3,4,18,27,33). How HMU, which is not contained within the GGCC sequence, affects the interaction between BsuR and Hi DNA is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…As with 4W-14 DNA, thymine and Y-Thy are formed from hmUra at the polynucleotide level (18). Normal levels of Y-Thy appear to be required for the replication and maturation of SP10 DNA; although not required absolutely for late gene expression, reduction of the level of Y-Thy in the DNA results in a reduced expression of the late genes (19). The glucosylation of hydroxymethylcytosine in T4 DNA is analogous to the conversion of hmUra to Y-Thy in SP10 and to putThy in XW-14.…”
mentioning
confidence: 99%